Reproduction system development of Ceracris kiangsu Tsai female adults and its relationship with fitness characteristics - Meizhi Wang; Meizhi Wang; Hongmei Li; Hongmei Li; Wei Zhang; Fuyan Zhuo; Tianjiao Li; Alyssa Lowry; Aihuan Zhang (Frontiers in Physiology, 2023)
Research on the ovarian development of insect pests helps provide key information for predicting pest occurrences, and currently, there is very limited information about the reproductive system of Ceracris kiangsu Tsai. This study aimed to assess the reproductive fitness of 321 adult female insects by using traditional methods to dissect female adults, measure female ovaries, and assess the process of egg formation. The phenotypic traits including body weight and body length were also measured and used to estimate the model of ovarian developmental stages. Four ovarian developmental stages before the oviposition were identified, and the fundamental ovarian structure of C. kiangsu displayed red dots on the matured eggs inside the calyx at ovarian developmental stage V. The accessory glands of C. kiangsu had the deepest folds at stage Ⅲ. Redundancy analysis (RDA) was used to explore the correlation between ovarian development, body weight, and body length. A significant positive correlation was observed for body weight (p = 0.001) and body length (p = 0.009), which varied with the grade of ovarian development evaluated by the ovarian developmental stage, ovarian length, ovarian width, and ovarian cross-sectional area. A partial least square (PLS) regression was used to model the ovarian developmental stage, with a stage-based PLS being identified as the more effective method, which was y = 1.509x1 + 0.114x2. The model provides a potentially rapid way to identify the population source as either “native” or “immigrant” from the phenotypic traits without dissection. The aforementioned model may be used to estimate adult emergence periods and identify migratory populations from their ovarian development, potentially aiding in implementing proper prevention measures.